Spatial Distribution of Telecom Masts, Accessibility and Customer Hotspots in the Greater Accra Metropolitan Area, Ghana - Emmanuel Yeboah; Isaac Sarfo; Michael Batame; Clement Kwang; Foster Kofi Addai; John Ernest Koku; Ben Aikins; Otoka Niabanga Dania Madeleina; Anita Boah (Archives of Current Research International, 2022)
Geographical distribution of telecommunication masts, patronage, and provision of quality services, without unintended consequences, remain vital for telecommunication operators. The spatial distribution of telecommunication masts and services in Ghana are not uniformly distributed, resulting in the disparities of signal strengths in different locations. Bad signals directly or indirectly affect various forms of business transactions and communication activities. We assessed the spatial distribution of telecom masts and customer hotspots for the major telecommunication networks in Ghana using geospatial techniques. Findings revealed most of the telecom masts were highly concentrated in Accra Metropolis. Again, most of the enterprise business customers were clustered within the 4-km radii of sited masts. More investment is needed by telecommunication industries to boost patronage, particularly in La Dade Kotopon and Tema Metropolis. The area’s prospect of attracting more customers increases sustainability concerns of telecommunication masts availability, accessibility, environmental health and management risks, among key industrial players.